Tinjauan Konseptual Kesatuan Dalam Keberagaman Terhadap Integrasi Nasional Berdasarkan Pemikiran Gus Mus - Nazila, Roudlotul; Sari, Anggun Puspita; Sya’diah, Badria Nikmatus; Anbiya, Bakti Fatwa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to analyze the concept of unity in diversity in the context of national integration according to Gus Mus's view. The approach used is a qualitative approach, namely a form of research approach that uses data in the form of narratives, story details, expressions and construction results from informants. The research method used is a literature review of books about Gus Mus' works or Gus Mus' lectures. The data validation technique uses source triangulation. The results of the analysis show that Gus Mus emphasizes the importance of understanding unity as an inclusive concept, which respects and strengthens diversity as a source of national wealth. Gus Mus's thoughts illustrate that sustainable national integration requires dialogue between various elements of society and the application of the principles of justice and togetherness. Through this literature study approach, this research presents an in-depth understanding of the concept of unity in diversity based on Gus Mus's thinking, as well as its implications for efforts to build strong and inclusive national integration in Indonesia.